Ultrasound guided intralesional bleomycin therapy for cystic lymphangioma in childhood - Pan, Pradyumna (International Journal of Contemporary Pediatrics, 2017)
Background: Lymphangiomas are benign hamartomatous lymphatic tumors, characterized by multiple communicating lymphatic channels and cystic spaces. They occur in nearly all regions of the body but are most frequently seen in the neck (75%), axilla (20%), and inguinal areas (2%). This study aims to evaluate the effectiveness of intralesional bleomycin sclerotherapy in the treatment of cystic lymphangioma in children and to determine the incidence of complications in the treatment. Methods: This is a prospective study of 36 children diagnosed with cystic lymphangioma and treated with intralesional injection of bleomycin aqueous solution from 2008 to 2015. Results: Complete resolution was seen in (16/36) of lesions, (17/36) had a good response and (3/36) had a poor response. The tumour recurred in 3 patients. No other serious complications or side effects were observed. Conclusions: Intralesional bleomycin therapy was very effective in the treatment of cystic lymphangioma. Our results were comparable to other published studies. Bleomycin administered as intralesional injection was found to be safe as there was no serious complication or side effect observed in this study.